Impact of Geographic Conditions on Sirri Marriage Phenomenon in Situbondo District - Singgih Susilo; Budijanto Budijanto; Ifan Deffinika; Novia Fitri Istiawati (Geosfera Indonesia, 2022)
This study aims to determine the impact of the geographical conditions of an area on the phenomenon of sirri marriage through a qualitative study. Data analysis was carried out inductively from the results of observations, in-depth interviews and FGDs. The results of the study indicate that the phenomenon of unregistered marriage occurs in Sumber Malang, Situbondo, East Java as a result of the geographical conditions of the area. The topographical conditions of the area in the form of mountainous areas with an altitude of 500-1,250 meters above sea level, very steep with a slope of 45%, rocky and dry soils make the Sumber Malang area difficult to develop economically. This is because agricultural cultivation is difficult to develop. Furthermore, the accessibility of areas that are difficult to reach because they are far inland, narrow roads, no public transportation, far from the center of economic activity have caused people in this area to choose to stay in their environment. Topography and regional accessibility have an impact on adolescent marriage behavior in the Sumber Malang community. Adolescents and parents view unregistered marriage as something that is done to avoid sin, the certainty of a relationship, economic motives (because the cost of marriage is considered expensive by the community) and as a result of the remote location of the area; because the teenager only has a circle of friends in Sumbermalang. There are two patterns of sirri marriage that occur, namely teenagers will marry sirri and live together and teenagers will marry sirri then stay with their parents and still continue their education. The implication of this research is to provide an illustration that geographical space can affect the pattern of marriage that occurs in society. Based on this, the relevant government can provide adequate access to education at the research sites. Keywords : Sirri's Marriage; geographical condition; topography; accessibility Copyright (c) 2022 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License